2010
DOI: 10.3184/095422910x12694549467335
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on calcium taurodeoxycholate micellar aggregates

Abstract: The formation of micellar aggregates in the presence of calcium(II) ions in solutions containing sodium and taurodeoxycholate ions and their composition at 25 C and in 0.5 mol dm À 3 N(CH 3 ) 4 Cl as constant ionic medium was studied. The study was carried out by means of two different procedures. In the first one, solid calcium oxalate was equilibrated with taurodeoxycholate, sodium and hydrogen ions and the free concentration of sodium and hydrogen ions was determined. After filtration, the calcium(II) (by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Previous , studies carried out on solutions containing calcium(II) and taurocholate and taurodeoxycholate showed that no precipitate is formed in a wide range of concentration, but only aggregates with different compositions.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous , studies carried out on solutions containing calcium(II) and taurocholate and taurodeoxycholate showed that no precipitate is formed in a wide range of concentration, but only aggregates with different compositions.…”
Section: Resultsmentioning
confidence: 97%
“…The protonation constants, k 1 , of the bile anions investigated here was previously determined in the same experimental conditions. 27 Previous 31,32 studies carried out on solutions containing calcium(II) and taurocholate and taurodeoxycholate showed that no precipitate is formed in a wide range of concentration, but only aggregates with different compositions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations